2019
DOI: 10.17148/iarjset.2019.6603
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Employability Skills of Graduate in Malaysian Interior Design

Abstract: The main objective of this research was to develop a framework for employability skills in interior design education curriculum. This research found three concepts of employability skills which include soft skills, hard skills and personal attributes from the literature. Also, from the survey, this research found framework which include of soft skills, hard skills and personal attribute skills which were later on merged to form the framework of employability skills. The discussions of findings were presented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The fixed teaching time in traditional teaching is no longer applicable, and the relatively stable teaching place has changed greatly in interior decoration design positions, and require the students majoring in interior design to write their own career plans to guide the long-term professional development of interior decoration design students [8][9]. On the platform of school-enterprise cooperation, we will vigorously promote the combination of work and study, closely contact the enterprises in the interior design industry, make full use of their respective superior resources to achieve mutual benefit and win-win development, realize the deep integration of college and interior design enterprises in talent training, and realize the seamless connection between college talent training and enterprise talent demand in the true sense [10].…”
Section: The Integration Of Production and Education Requires The Tra...mentioning
confidence: 99%
“…The fixed teaching time in traditional teaching is no longer applicable, and the relatively stable teaching place has changed greatly in interior decoration design positions, and require the students majoring in interior design to write their own career plans to guide the long-term professional development of interior decoration design students [8][9]. On the platform of school-enterprise cooperation, we will vigorously promote the combination of work and study, closely contact the enterprises in the interior design industry, make full use of their respective superior resources to achieve mutual benefit and win-win development, realize the deep integration of college and interior design enterprises in talent training, and realize the seamless connection between college talent training and enterprise talent demand in the true sense [10].…”
Section: The Integration Of Production and Education Requires The Tra...mentioning
confidence: 99%
“…Huber and Waxman suggested that students should gain experience outside the classroom because entrylevel interior designers are likely to work in a variety of tasks within the profession and, therefore, should build the personal skills and experiences that support their formal education and are consistent with their profession goals (Huber and Waxman, 2019). Deficits in graduate competencies that are required by employers cause difficulties in obtaining a job (Ntinyari, 2014) and cost the employer in terms of training expenses and on-boarding time (Huber and Waxman, 2019;Ntinyari, 2014); employers, ultimately, need graduates who are ready to work and have the appropriate experience (Alrifa and Raju, 2019;Huber and Waxman, 2019).…”
Section: Professional Practices In Interior Designmentioning
confidence: 99%
“…Meanwhile, Alrifa and Raju (2019) undertook to develop a framework for employment skills in interior design education and determine the relationship between design graduate skills and employer satisfaction. The study highlighted that interior designers should have soft skills "communication skills, problem-solving skills, teamwork skills" and hard skills "style skills, project management skills, and computer skills", in addition to personal attributes and skills that focus on more practical training.…”
Section: Higher Education Outcomes and The Labour Marketmentioning
confidence: 99%
See 1 more Smart Citation